The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1101/2020.01.15.908293
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

WNT and inflammatory signaling distinguish human Fallopian tube epithelial cell populations

Abstract: A substantial fraction of ovarian/extra-uterine high-grade serous carcinomas (HGSCs) likely originate in the distal region of the Fallopian tube's epithelium (TE) before implanting/metastasizing to the ovary. Unfortunately, molecular and cellular mechanisms rendering preferential cancer susceptibility of the human distal TE remain insufficiently elucidated, largely due to limited primary human TE gene expression data. Here we report an in depth bioinformatic characterization of 34 primary TE cell mRNA-seq s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 45 publications
(55 reference statements)
1
10
0
Order By: Relevance
“…4A). These GO terms are similar to previously published datasets from other mammals, including cows and humans, where vesicle-mediated transport, endocytosis, and exocytosis were among the main processes enriched in the posterior (Gonella-Diaza et al, 2017;Maillo et al, 2016;Rose et al, 2020). We confirmed this trend using qPCR for a transport ATPase (Atp1b1) and a solute carrier (Slc39a8); both were significantly enriched in the posterior (Fig.…”
Section: The Mouse Oviduct Displays Robust Transcriptional Patterningsupporting
confidence: 90%
“…4A). These GO terms are similar to previously published datasets from other mammals, including cows and humans, where vesicle-mediated transport, endocytosis, and exocytosis were among the main processes enriched in the posterior (Gonella-Diaza et al, 2017;Maillo et al, 2016;Rose et al, 2020). We confirmed this trend using qPCR for a transport ATPase (Atp1b1) and a solute carrier (Slc39a8); both were significantly enriched in the posterior (Fig.…”
Section: The Mouse Oviduct Displays Robust Transcriptional Patterningsupporting
confidence: 90%
“…Although definitive markers for FT stem/progenitor cells remain elusive, Rose et al found an Aldh+ subpopulation enriched for stem/progenitor-like cells (38), and Dinh et al have identified a progenitor-like subset with high expression of Thy1, Igfbp5, and Lgals1 (41). Moreover, Wnt and Notch pathways are reported to maintain FT stemness (35, 38, 42).…”
Section: Resultsmentioning
confidence: 99%
“…Although definitive markers for FT stem/progenitor cells remain elusive, Rose et al found an Aldh+ subpopulation enriched for stem/progenitor-like cells (38), and Dinh et al have identified a progenitor-like subset with high expression of Thy1, Igfbp5, and Lgals1 (41). Moreover, Wnt and Notch pathways are reported to maintain FT stemness (35, 38, 42). To compare these candidate markers and pathways between small and expanded clones, we isolated them separately from MADM-wildtype mice using fluorescence-guided laser capture microdissection (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations